Diagnosis and Treatment of Pediatric Necrotizing Fasciitis: A Systematic Review of the Literature - Zundel, Sabine; Lemaréchal, Angela; Kaiser, Philipp; Szavay, Philipp (European Journal of Pediatric Surgery, 2017)
Introduction Pediatric necrotizing fasciitis (NF) is a rare but severe, life-threatening infection. Early diagnosis is crucial to reduce morbidity and mortality, but initial symptoms are nonspecific. Little sound data exists on factors aiding clinicians to recognize NF in children. With a systematic literature review, we aimed to better characterize pediatric NF. We focused on triggers, symptoms, and laboratory and microbiological findings and differences between pediatric adult patients.Materials and Methods A literature research was conducted according to the guidance of the “Preferred Reporting Items for Systematic Reviews and Meta-Analyses.” Articles published between January 2010 and October 2015 were included. Data extraction was performed as an iterative process.Results A total of 32 articles describing 53 pediatric patients with NF were included in the analysis. Overall mortality was 15.4%. Frequency peaks were found for neonates and children aged between 1 and 2 years. These two age groups were predominantly affected on the torso. Another frequency peak was found in patients aged around 10 years of age. These patients were predominantly affected on the extremities and face. In general, early symptoms were found to be fever, erythema, localized selling, and tenderness or pain. “Pain out of proportion” was not mentioned as a typical symptom. Fever and leukocytosis were more common in teenage patients. Monomicrobial necrotizing (type 2) fasciitis was much more common than polymicrobial (type 1) fasciitis. Next to Streptococci and Staphylococci, Pseudomonas aeruginosa was often isolated. Early aggressive surgical treatment was the treatment of choice.Conclusions Pediatric NF has distinguishing features that differ from adult NF. Knowledge of these details should increase early diagnosis and improve treatment.
Keywords: necrotizing fasciitis; pseudomonas; pediatric; child